2021
DOI: 10.1016/j.phro.2021.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Automated clinical target volume delineation using deep 3D neural networks in radiation therapy of Non-small Cell Lung Cancer

Abstract: Background and purpose Clinical targeted volume (CTV) delineation accounting for the patient-specific microscopic tumor spread can be a difficult step in defining the treatment volume. We developed an intelligent and automated CTV delineation system for locally advanced non-small cell lung carcinoma (NSCLC) to cover the microscopic tumor spread while avoiding organs-at-risk (OAR). Materials and methods A 3D UNet with a customized loss function was used, which takes both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Recent studies have elicited dose–response relationships for several component structures [15] , [16] , [17] , [18] , [19] , [20] and trials are underway to test the effect of sparing these regions [30] . As the application of artificial intelligence is explored in RT, volume delineation serves as a logical starting point [31] , [32] , [33] . By accurately performing complex and time-consuming delineation tasks, clinician availability for alternate activities could be increased and treatment planning delays reduced [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have elicited dose–response relationships for several component structures [15] , [16] , [17] , [18] , [19] , [20] and trials are underway to test the effect of sparing these regions [30] . As the application of artificial intelligence is explored in RT, volume delineation serves as a logical starting point [31] , [32] , [33] . By accurately performing complex and time-consuming delineation tasks, clinician availability for alternate activities could be increased and treatment planning delays reduced [34] .…”
Section: Discussionmentioning
confidence: 99%
“…17 Kawula et al trained a model using an in-house algorithm, and demonstrated DSC of 0.87, 0.97, and 0.89 for prostate, bladder, and rectum, respectively. 18 In addition to prostate cancer, CT-based DL auto-segmentation models have also been reported for other disease sites, such as brain, 19,20 head and neck, 21,22 lung, [23][24][25][26] breast, 27 esophagus, 28 liver, [29][30][31] pancreas, 32 bladder, 33 and gynecological cancers. 34,35 While the prior studies have demonstrated the feasibility of constructing DL models to automate the tedious contouring task in prostate treatment planning, the applicability of each model is limited by clinical protocol, particularly the immobilization method which can affect the shape and position of key organs.…”
Section: Introductionmentioning
confidence: 99%
“…trained a model using an in‐house algorithm, and demonstrated DSC of 0.87, 0.97, and 0.89 for prostate, bladder, and rectum, respectively 18 . In addition to prostate cancer, CT‐based DL auto‐segmentation models have also been reported for other disease sites, such as brain, 19,20 head and neck, 21,22 lung, 23–26 breast, 27 esophagus, 28 liver, 29–31 pancreas, 32 bladder, 33 and gynecological cancers 34,35 …”
Section: Introductionmentioning
confidence: 99%
“…The one-day workflow proposed by Palacios et al [2] used automation only to a minor extent and it is therefore highly dependent on the availability of staff throughout the day and not easily scalable to increasing patient numbers. Automated tools for various steps in the radiotherapy planning workflow such as automatic contouring [4] , [5] , [6] , [7] , [8] and radiotherapy planning [9] , [10] , [11] , [12] , [13] recently gained attention. For instance, Johnston et al [7] showed the usability of a convolutional neural network for segmentation of thoracic organs at risk.…”
mentioning
confidence: 99%
“…For instance, Johnston et al [7] showed the usability of a convolutional neural network for segmentation of thoracic organs at risk. Although auto-contouring of targets is more challenging, Xie et al [8] recently introduced a 3D neural network for lung lesion contouring. Also, for treatment plan optimization different approaches were proposed [9] , [10] , [11] , [12] , [13] .…”
mentioning
confidence: 99%